COMPARATIVE AND CONTRASTIVE LINGUISTICS: MEDIA LINGUISTICS AND LINGUISTIC RESEARCH (Ustozlar uchun, 2026)
This thesis explores the role of comparative and contrastive linguistics within media linguistics. It analyzes how different languages employ linguistic strategies in media discourse. The research highlights cultural, ideological, and communicative differences reflected in media texts.